Mobilizing Climate Information for Decision-Making in Africa: Contrasting User-Centered and Knowledge-Centered Approaches - Harvey, Blane; Huang, Ying-Syuan; Araujo, Julio; Vincent, Katharine; Roux, Jean-Pierre; Rouhaud, Estelle; Visman, Emma (Frontiers in Climate, 2021)
This study examined ways in which climate information was mobilized for use under Future Climate for Africa (FCFA), an applied research program to improve the use of medium term (5-40 year) climate information in policies and planning in sub-Saharan Africa. Past research has underscored the interdependent relationship between user engagement and knowledge mobilization in effective climate knowledge uptake. Following existing frameworks for user engagement and knowledge mobilization, we undertook document analysis of 46 program outputs and semi-structured interviews with 13 FCFA researchers to contrast user-centred and knowledge-centred approaches, embedded within co-production principles, to effectively mobilize climate information uptake for use. A total of 20 knowledge mobilization tools and approaches were identified across the program, which map onto four categories. This analysis revealed a complex interplay between user engagement and knowledge mobilization processes, which sheds light on a strategic or flexible use and re-use of knowledge products as the user engagement process evolved. These findings have important implications for future programmatic design and planning in promoting engagement and mobilization approaches that can contribute to long-term policy and decision-making.